Answer:
18x^2-23x-6
Step-by-step explanation:
multiply: 9x*2x-9x*3+2*2x-2*3
18x^2-9X(3)3+2(2X)-2(3)
18X^2-27x+4x-6
18x^2-23x-6
Answer:
The value of the expression 2*-2-(3- -2) is -9.
Step-by-step explanation:
2 x (-2)- (3- -2)
=2 x (-2)- (3+2)
=2 x (-2) -5
= -4-5
=<u><em>-9</em></u>
Hope this Helps!!!
Please consider this as brainliest, thanks!!!
She spends 14 days in Texas
Answer: 9,000
Step-by-step explanation: there are 9 number options for the first digit and 10 for the other 3, so 9x10x10x10=9000
Answer:
1. multiplication property of equality
2. division property of equality
Step-by-step explanation:
1. multplied by -3/2
2. divided by -2/3